مشكلة ترجمة النصوص العربية للطلبة بالمدرسة المتوسطة الاسلامية الحكومية الثانية بنجكولو - Nur Haryanto (UIN Fatmawati Sukarno Bengkulu, 2018)
Teaching materials in the teaching of Arabic in middle school One of them is the translation of some short and long sentence, as in the conversations and topics of choice that fit the curriculum. It is also taught to students of simple Arabic wholesale. However, from the information obtained by the researcher from the Arabic teacher he says that the students could not master this skill, this situation can be seen from their duties in translating the Arabic language into Indonesian language still suffer from limitations in the syntax of the sentences and the choice of words in the particular expression. The difficulty of the text can be related to the translator's level of ability. There are two things that are interrelated: the text is easy because the translator's level of ability is very good, or the text is difficult because the translator's level of ability is still very low. This background is what drives the researcher to look into the problem of translation that is happening to students at the second Inter-Governmental Secondary School Bengkulu. The researcher uses a method of qualitative descriptive method. Research subordinates are students in the second semester of the second Islamic secondary school Bengkulu. The method of collecting data used by the researcher is interview, observation and documentation. Data analysis used is data collection, data identification, data presentation and data mining. The results of the research obtained by the researcher are from the data collected by the researcher, whether from the interviews, observations and documentation obtained by the researcher, the problems faced by students in translating the Arabic texts into the Indonesian language of students in the second semester in the second intermediate Islamic Islamic State School Bengkulu are two main problems, namely the linguistic problem and the non-linguistic problem